An evaluation of excrement as an alternative to blood for characterizing lead exposure in bald eagles - William J. Reiter‐Marolf; Stephen J. Dinsmore; Julie A. Blanchong (Wildlife Society Bulletin)
ABSTRACT Lead (Pb) exposure in free‐flying bald eagles (Haliaeetus leucocephalus) is an important conservation concern. One of the challenges to characterizing the magnitude of Pb exposure in free‐flying bald eagles is obtaining samples. Although blood samples are the most commonly used biomarker to quantify Pb exposure in living animals, the potential for negative impacts resulting from handling bald eagles make blood sampling less than ideal in a large‐scale field study. We partnered with wildlife rehabilitators, who simultaneously collected blood and excrement samples from bald eagles admitted for rehabilitation in Iowa, USA, 2012 and 2013, to determine whether excrement could provide information comparable to blood about Pb exposure. We used linear regression to examine the relationship between excrement and blood Pb levels from 45 bald eagles admitted for rehabilitation and found that excrement Pb levels were statistically significantly related to blood Pb levels (P < 0.01, R2 = 0.68). Specifically, when excrement Pb levels were low, blood Pb levels were also low. We also found patterns in Pb levels as a function of sex, age, season admitted, and fate. We conclude that excrement has the potential to be a valuable tool for investigating Pb exposure in bald eagles. © 2015 The Wildlife Society.